THE BALANCE BETWEEN ACADEMIC ACTIVITIES AND MENTAL HEALTH IN HIGH SCHOOL ADOLESCENTS: CHALLENGES AND SOLUTIONS - Azizah Choirunisa; Bilqiis Keisha Rizki Lubis; Cahaya Nafila; Fadilla Dwi Ramadhani; Maiza Rafifa Sari Daulay (PT. Radja Intercontinental Publishing, 2024)
Adolescents at the high school level today often experience high academic pressure. The large demands faced by adolescents today make their inability to adapt to these demands which causes adolescents to experience mental health disorders. Based on Law Number 18 of 2014 concerning Mental Health, it is stated that Mental Health Efforts are every activity aimed at realizing the optimal degree of mental health for each individual, family, and community through promotive, preventive, curative, and rehabilitative services that are implemented in an integrated, sustainable, and comprehensive manner by the government, local government, or community. Therefore, the balance between academic activities and student health is a significant challenge that requires an integrated solution. Research techniques include the use of relevant scientific and academic databases, development of search strategies, establishment of inclusion and exclusion criteria, and implementation of thorough literature search and selection procedures. Optimizing the balance between academic activities and mental well-being of secondary school students is an important determining factor in improving their overall health and academic performance.